Managing waste product of palm oil mill (decanter cake) as compost / Nik Aidil Bariqi Nik Roslan, Muhammad Izzat Fikri Hasim and Soliah Azman - Nik Roslan, Nik Aidil Bariqi; Hasim, Muhammad Izzat Fikri; Azman, Soliah (Faculty of Plantation and Agrotechnology, 2023)
One of Malaysia's crucial industries is the oil palm sector. Due to the huge demand from other nations, palm oil output keeps growing year after year, producing a lot of trash from the field and the mill. This waste could have a big impact on the ecosystem. One way to reduce the amount of waste produced is by composting. Due to the qualities that have been improved during the composting process, compost material is widely employed, particularly in agricultural activities. Empty fruit bunch (EFB) compost primarily functions as mulch to keep the soil moist and acts as organic fertilizer because it is rich in nutrients that the plant needs to grow.